Our commencement - Corlett, Christine Mossman (My University, 1891)
Introduction: It is peculiarly appropriate at this season of our lives that we ask ourselves what commencement is. Probably not one of the many young people who have “fought the good fight, finished the course,” and stepped out from the college halls all over this broad land, but has asked this question. Some perhaps lightly, thinking of nothing more than flowers, music, applause, and a diploma. But the most have asked it thoughtfully, pondering long and deeply on its meaning. To this latter class commencement means more than flowers, more than music, more than applause or a diploma. There are only the pleasant accompaniments of the beginning of their true life—not only of their true life, but of a higher and grander education than any they have hers-to-fore known. We have studied algebra in college. We now take the unknown quantities of geologic ages, solve the equations and get the known results—the scent of the plants, the power and adaptability of soils—till even the history of the books shall help us in our struggle to subdue the earth. We have studied geometry as it is taught in schools. We now have the whole heavens spread out before us in a more magnificent geometry than finite mind has ever yet conceived.
Citation: Corlett, Christine Mossman. Our commencement. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Commencement; Education; Gaduation; College; Theses; Manuscripts (documents)